2015
DOI: 10.1080/10426507.2014.974749
|View full text |Cite
|
Sign up to set email alerts
|

CeCl3.7H2O-SiO2 Catalyzed Ultrasonicated Solvent-Free Synthesis of Carbamoyl/Carbamothioyl Phosphonates and Antimicrobial Activity Evaluation

Abstract: Running head: CeCl 3 .7H 2 O-SiO 2 catalysed solvent-free synthesis for P-C=(O,S) derivatives ABSTRACT An expeditious and green method has been developed for the synthesis of a series of P-C bond derivatives, diethyl substituted phenylcarbamoylphosphonates 6(a-e)/ phenylcarbamothioylphosphonates 7(a-f) in high yields via simple addition reaction of isocyanates/isothiocyanates with diethyl phosphite in the presence of silica supported Lewis acid catalyst, SiO 2 -CeCl 3 .7H 2 O under solvent-free and sonication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…There are few descriptions of biological testing of arylcarbamoyl‐phosphonates like compound 3 in the literature. The scaffold has been examined as antimicrobials, [18] Src SH2 domain ligands, [19] anti‐tumor agents [20] and human thyroid hormone agonists [21] . A recent paper published after this work was completed revealed that N ‐(4‐chlorophenylcarbamoyl)phosphonic acid possessed weak antimicrobial activity as well as some analgesic activity in multiple animal pain models [22] .…”
Section: Discussionmentioning
confidence: 99%
“…There are few descriptions of biological testing of arylcarbamoyl‐phosphonates like compound 3 in the literature. The scaffold has been examined as antimicrobials, [18] Src SH2 domain ligands, [19] anti‐tumor agents [20] and human thyroid hormone agonists [21] . A recent paper published after this work was completed revealed that N ‐(4‐chlorophenylcarbamoyl)phosphonic acid possessed weak antimicrobial activity as well as some analgesic activity in multiple animal pain models [22] .…”
Section: Discussionmentioning
confidence: 99%
“…9 Raju et al developed the silica-supported Lewis acid catalyst SiO 2 -CeCl 3 •7H 2 O to synthesize CPOs via the addition of diethyl phosphite to aromatic isocyanates under heating or ultrasonication conditions. 10 Challenges still exist despite these recent advances, such as high catalyst loading, low yields of the desired products, long reaction times, limited scope of isocyanates, and harsh conditions. Therefore, the development of highly efficient catalysts for the preparation of CPOs under mild conditions is still strongly required.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Kaboudin and co-workers found that 0.1 equiv of anhydrous calcium chloride as a Lewis base catalyst can promote the addition reaction to prepare CPOs in moderate yields (≤65%) . Raju et al developed the silica-supported Lewis acid catalyst SiO 2 -CeCl 3 ·7H 2 O to synthesize CPOs via the addition of diethyl phosphite to aromatic isocyanates under heating or ultrasonication conditions . Challenges still exist despite these recent advances, such as high catalyst loading, low yields of the desired products, long reaction times, limited scope of isocyanates, and harsh conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In synthetic chemistry, green methods are attracting interest because of their environmental benefits. 1 Such methods include catalyst free, 2 supercritical fluids, 3 water-phase reactions, 4 ionic liquids, 5 solvent-free reactions, 6 metal-free 7 and ultrasound 8 or microwaves irradiation. 9 Nitrogen-containing heterocycles have also proved attractive andthey have been widely used in the medicinal, agricultural and industrial fields.…”
mentioning
confidence: 99%